PARADIGMA EPISTEMOLOGI ISLAM: BAYANI, BURHANI, IRFANI, DAN RELEVANSINYA DALAM DUNIA MODERN - Thufeil Abyan Ahmad; Eva Dewi; Athiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
. Islamic epistemology is the study of the sources, methods, and validity of knowledge within the Islamic scientific tradition. One well-known mapping of Islamic epistemology is the bayani, burhani, and irfani paradigms introduced by Muhammad Abid al-Jabiri. This study aims to examine the concept of Islamic epistemology through the bayani, burhani, and irfani paradigms, and to analyze their relevance and integration in the modern world. This study employed a library research method with a descriptive qualitative approach. Data were obtained from various literature in the form of books, scientific articles, and academic works related to Islamic epistemology, then analyzed using content analysis techniques. The results of the study indicate that the bayani paradigm serves as a normative foundation that maintains the authority of revelation and moral values. The burhani paradigm serves as a foundation for the development of science and technology through a rational-empirical approach. While the irfani paradigm plays a role in fulfilling human spiritual needs through the development of inner awareness and the search for the meaning of life. These three paradigms are not contradictory, but rather complementary in building a comprehensive Islamic epistemological system that is relevant to the challenges of the modern world. Therefore, the integration of bayani, burhani, and irfani is necessary to build a holistic, balanced Islamic epistemology capable of contributing to the development of science and contemporary human civilization.